Novel vertically stacked Ge0.85Si0.15 nGAAFETs above a Si channel with low SS of 76 mV/dec by underneath Si channel and enhanced Ion (1.7X at VOV = VDS = 0.5 V) by Ge0.85Si0.15 channels. (31st March 2020) - Liu, Yi-Chun; Huang, Yu-Shiang; Lu, Fang-Liang; Ye, Hung-Yu; Tu, Chien-Te; Liu, C W
Abstract: An engineering solution is provided to improve the electrostatic behaviors of Ge-based channels gate-all-around FETs. We demonstrate the vertically stacked Ge0.85 Si0.15 channels above a Si channel, which has good subthreshold behaviors. The two Ge0.85 Si0.15 channels are tensily strained to improve I on . With optimized channel dimensions, the threshold voltage of Ge0.85 Si0.15 channels is more positive than the Si channel by quantum confinement. Therefore, the underneath Si channel with good electrostatic control dominates the subthreshold region. Good subthreshold slope = 76 mV/dec and low drain-induced barrier lowering = 36 mV/V are achieved. For on-state, the stacked high-mobility GeSi channels turn on after the Si channel to achieve I on of 13.9 μ A per stack at V OV = V DS = 0.5 V.